Pulsar polarisation below 200 MHz: Average profiles and propagation effects - Noutsos, A.; Sobey, C.; Kondratiev, V.; Weltevrede, P.; Verbiest, J.; Karastergiou, A.; Kramer, M.; Kuniyoshi, M.; Alexov, A.; Breton, R.; Bilous, A.; Cooper, S.; et al. (EDP Sciences, 2015)
Aims: We present the highest-quality polarisation profiles to date of 16 non-recycled pulsars and four millisecond pulsars, observed below 200 MHz with the LOFAR high-band antennas. Based on the observed profiles, we perform an initial investigation of expected observational effects resulting from the propagation of polarised emission in the pulsar magnetosphere and the interstellar medium. Methods: The polarisation data presented in this paper have been calibrated for the geometric-projection and beam-shape effects that distort the polarised information as detected with the LOFAR antennas. We have used RM Synthesis to determine the amount of Faraday rotation in the data at the time of the observations. The ionospheric contribution to the measured Faraday rotation was estimated using a model of the ionosphere. To study the propagation effects, we have compared our low-frequency polarisation observations with archival data at 240, 400, 600, and 1400 MHz. Results: The predictions of magnetospheric birefringence in pulsars have been tested using spectra of the pulse width and fractional polarisation from multifrequency data. The derived spectra offer only partial support for the expected effects of birefringence on the polarisation properties, with only about half of our sample being consistent with the model's predictions. It is noted that for some pulsars these measurements are contaminated by the effects of interstellar scattering. For a number of pulsars in our sample, we have observed significant variations in the amount of Faraday rotation as a function of pulse phase, which is possibly an artefact of scattering.These variations are typically two orders of magnitude smaller than that observed at 1400 MHz by Noutsos et al. (2009), for a different sample of southern pulsars. In this paper we present a possible explanation for the difference in magnitude of this effect between the two frequencies, based on scattering. Finally, we have estimated the magnetospheric emission heights of low-frequency radiation from four pulsars, based on the phase lags between the flux-density and the PA profiles, and the theoretical framework of Blaskiewicz et al. (1991, ApJ, 370, 643). These estimates yielded heights of a few hundred km; at least for PSR B1133+16, this is consistent with emission heights derived based on radius-to-frequency mapping, but is up to a few times larger than the recent upper limit based on pulsar timing. Conclusions: Our work has shown that models, like magnetospheric birefringence, cannot be the sole explanation for the complex polarisation behaviour of pulsars. On the other hand, we have reinforced the claim that interstellar scattering can introduce a rotation of the PA with frequency that is indistinguishable from Faraday rotation and also varies as a function of pulse phase. In one case, the derived emission heights appear to be consistent with the predictions of radius-to-frequency mapping at 150 MHz, although this interpretation is subject to a number of systematic uncertainties.